Molecular characterization of mutations associated with resistance to second line drugs in Mycobacterium tuberculosis patients from Casablanca, Morocco - Momen, Ghizlane; Achraf, Aainouss; Abdelmajid, Lamaammal; Fouad, Chetioui; Mohamed, Blaghen; Malika, Messaoudi; Khalid, Belghmi; Jamal, Mouslim; Mohammed, El Mzibri; Driss, EL Messaoudi My; Meriem, Khyatti; Imane, Chaoui (Revista do Instituto de Medicina Tropical de São Paulo, 2021)
The emergence and spread of extensively drug-resistant tuberculosis (XDR-TB) is a serious threat to global health. Therefore, its rapid diagnosis is crucial. The present study aimed to characterize mutations conferring resistance to second line drugs (SLDs) within multidrug Mycobacterium tuberculosis (MDR-MTB) isolates and to estimate the occurrence of XDR-TB in Casablanca, Morocco. A panel of 200 MDR-TB isolates was collected at the Pasteur Institute between 2015-2018. Samples were subjected to drug susceptibility testing to Ofloxacin (OFX), Kanamycin (KAN) and Amikacin (AMK). The mutational status of gyrA, gyrB, rrs, tlyA and eis was assessed by sequencing these target genes. Drug susceptibility testing for SLDs showed that among the 200 MDR strains, 20% were resistant to OFX, 2.5% to KAN and 1.5% to AMK. Overall, 14.5% of MDR strains harbored mutations in gyrA, gyrB, rrs and tlyA genes. From the 40 OFXR isolates, 67.5% had mutations in QRDR of gyrA and gyrB genes, the most frequent one being Ala90Val in gyrA gene. Of note, none of the isolates harbored simultaneously mutations in gyrA and gyrB genes. In eight out of the 200 MDR-TB isolates resistant either to KAN or AMK, only 25% had A1401G or Lys89Glu change in rrs and tlyA genes respectively. This study is very informative and provides data on the alarming rate of fluoroquinolone resistance which warrants the need to implement appropriate drug regimens to prevent the emergence and spread of more severe forms of Mycobacterium tuberculosis drug resistance.